EXPERIMENTAL DIABETES MELLITUS INFLUENCE ON BREASTBONE AND COSTAL COMPLEX AND ITS RESULT - Ibrahimova Lobar Ibrohimovna; Salimjonov Mukhammadjon Zafarjon ugli (Scholar Express Journals, 2022)
The purpose of the work was to study the dynamics of morphological and structural changes in the toe- nail cortex of the rats offspring with diabetes mellitus with alloxane.
Keywords: Cartilage; Alloxane; Experimental Diabetes Mellitus; Chondrocyte